Психоэмоциональные особенности женщин с алопецией = Psychoemotional characteristicsin women with alopecia - Zhyvylko, V. V. (Journal of Education, Health and Sport, 2015)
Zhyvylko V. V. Психоэмоциональные особенности женщин с алопецией = Psychoemotional characteristicsin women with alopecia. Journal of Education, Health and Sport. 2015;5(12):775-782. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.54576 http://ojs.ukw.edu.pl/index.php/johs/article/view/3540 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport (null) 2391-8306 7 © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.12.2015. Revised 25.12.2015. Accepted: 29.12.2015. УДК616.594.14-06:616.8]-055.2-085.851 ПСИХОЭМОЦИОНАЛЬНЫЕ ОСОБЕННОСТИ ЖЕНЩИН С АЛОПЕЦИЕЙ В. В. Живилко Одесский национальный медицинский университет Реферат. В статье приведены результаты исследования эмоциональной сферы женщин, больных алопецией. Одним из основных этиологических факторов дерматологических заболеваний является непосредственное влияние психоэмоционального состояния больного. Вместе с тем алопеция сопровождается значительными изменениями внешности, не желательной реакцией окружающих людей, длительным лечением, частыми рецидивами и срывами лечебного процесса, что, в свою очередь, может вызвать угнетение эмоционального состояния больного. Это в значительной степени влияет на эффективность лечения. Ключевые слова: алопеция, эмоциональная сфера, тревожность, депрессия, невротизация, агрессивность. PSYCHOEMOTIONAL CHARACTERISTICSIN WOMEN WITH ALOPECIA V. V. Zhyvylko Odessa National Medical University, Odessa, Ukraine The peculiarities of alopecia women have been analyzed. It has been pointed out that the patient’s psycho-emotional condition direct impact isone of the main etiological factors of dermatological diseases. Alopecia is accompanied by significant changes in appearance, undesirable reaction of the surrounding persons, long-term treatment, frequent relapses and breakdowns of the treatment process, which, in their turn, can cause suppression of the emotional state of the patient and to a large extent influence the efficacy of the treatment. Key words: alopecia, emotional sphere, anxiety, depression, neuroticism, aggression.